2019
DOI: 10.1111/pcn.12914
|View full text |Cite
|
Sign up to set email alerts
|

Nalmefene in alcohol‐dependent patients with a high drinking risk: Randomized controlled trial

Abstract: AimsReducing alcohol consumption is one treatment approach for alcohol‐dependent patients. This study compared nalmefene 20 mg and 10 mg with placebo, combined with psychosocial support, in alcohol‐dependent Japanese patients with a high or very high drinking risk level (DRL).MethodsThis was a multicenter, randomized, double‐blind, phase 3 study conducted in alcohol‐dependent patients with a high or very high DRL. Patients were randomized to 24 weeks of treatment with as‐needed nalmefene 20 mg, 10 mg, or place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
23
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 30 publications
(41 reference statements)
1
23
0
4
Order By: Relevance
“…Quality of Life was evaluated in our study, and a significant difference was found between placebo and Nalmefene groups at 12 weeks for the Alcohol Quality of Life Scale (AQOLs) evaluation . However, as Palpacuer and colleagues pointed out, no significant differences were found between placebo and Nalmefene groups at 24 weeks for AQOLs, SF‐36 and EQ‐5D evaluations .…”
mentioning
confidence: 45%
See 3 more Smart Citations
“…Quality of Life was evaluated in our study, and a significant difference was found between placebo and Nalmefene groups at 12 weeks for the Alcohol Quality of Life Scale (AQOLs) evaluation . However, as Palpacuer and colleagues pointed out, no significant differences were found between placebo and Nalmefene groups at 24 weeks for AQOLs, SF‐36 and EQ‐5D evaluations .…”
mentioning
confidence: 45%
“…First, we fully understand the issue of attrition bias and had mentioned this as a limitation in our paper . We also performed two kinds of imputation analyses and it was shown that heavy drinking day (HDD) and total alcohol consumption (TAC), the main analyses, were robust with sensitivity analysis complementing missing data …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, subgroup analyses are only exploratory. It is therefore reasonable to question if the new RCT assessing the efficacy of nalmefene in patients with a high drinking risk can add to the previous body of evidence. We argue that this study shares the weaknesses of the previous phase 3 trials that led to questioning the efficacy of nalmefene in reducing alcohol consumption …”
mentioning
confidence: 99%